2019
DOI: 10.1007/s00464-019-07170-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term outcomes of robotic rectal surgery—from the real word data of 1145 consecutive cases in China

Abstract: Background Due to a limited patient sample size, substantial data on robotic rectal resection (RRR) is lacking. Here, we reported a large consecutive cases from the real word data to assess the safety and efficacy of RRR. Methods From September 2010 to June 2017, a total of 1145 consecutive RRR procedures were performed in patients with stage I-IV disease. We conducted an analysis based on information from a prospectively designed database to evaluate surgical outcomes, urogenital function, and long-term oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
4
22
2
Order By: Relevance
“…46 Chang et al reported no cases of incomplete mesorectum in their study of 1,145 cases of robotic rectal surgery, and Alfieri et al reported 98.3% of complete or near complete mesorectum. 26,61 These results, although comparable with those of LaTME, are very satisfactory and validate the safety of TME. 19,45 Functional Outcomes Urinary and sexual dysfunction are well-known sequelae, whether temporary or definitive, of rectal cancer surgery, due to unintentional injury or excision of pelvic autonomic nerves.…”
Section: Distal and Proximal Resection Marginssupporting
confidence: 67%
See 3 more Smart Citations
“…46 Chang et al reported no cases of incomplete mesorectum in their study of 1,145 cases of robotic rectal surgery, and Alfieri et al reported 98.3% of complete or near complete mesorectum. 26,61 These results, although comparable with those of LaTME, are very satisfactory and validate the safety of TME. 19,45 Functional Outcomes Urinary and sexual dysfunction are well-known sequelae, whether temporary or definitive, of rectal cancer surgery, due to unintentional injury or excision of pelvic autonomic nerves.…”
Section: Distal and Proximal Resection Marginssupporting
confidence: 67%
“…5 cm, were not significant in this study. 61 Tsukamoto et al, in a multi-center pilot phase II study with 50 cases, reported similar overall and severe complication rates (16% and 4%, respectively) with anastomotic leakage being the most common complication. The authors suggest that the low complication rate may be associated, among others, with the robotic system characteristics that allow better visualization and mobilization, precise dissection and safe reconstruction.…”
Section: Complicationsmentioning
confidence: 81%
See 2 more Smart Citations
“…Some studies have reported no difference in the incidence of complications between robotic surgery and traditional laparoscopic surgery ( 9 ). Since 2010, the robotic surgery system has been gradually applied to radical surgery for mid and low rectal cancer due to its capability of producing high-definition images and its stable and flexible operation ( 10 ). These features are advantageous in distinguishing pelvic nerves, dissecting the anterior and lateral tissues, and suturing.…”
Section: Discussionmentioning
confidence: 99%